Identification of a brefeldin A-insensitive guanine nucleotide-exchange protein for ADP-ribosylation factor in bovine brain. - Tsai, S C (1994)
ADP-ribosylation factors (ARFs) are approximately 20-kDa guanine nucleotide-binding proteins that participate in vesicular transport in the Golgi and other intracellular compartments and stimulate cholera toxin ADP-ribosyltransferase activity. ARFs are active in the GTP-bound form; hydrolysis of bound GTP to GDP, possibly with the assistance of a GTP hydrolysis (GTPase)-activating protein results in inactivation. Exchange of GDP for GTP and reactivation were shown by other workers to be enhanced by Golgi membranes in a brefeldin A-sensitive reaction, leading to the proposal that the guanine nucleotide-exchange protein (GEP) was a target of brefeldin A. In the studies reported here, a soluble GEP was partially purified from bovine brain. Exchange of nucleotide on ARFs 1 and 3, based on increased ARF activity in a toxin assay and stimulation of binding of guanosine 5'-[gamma-[35S]thio]triphosphate, was dependent on phospholipids, with phosphatidylserine being more effective than cardiolipin. GEP appeared to increase the rate of nucleotide exchange but did not affect the affinity of ARF for GTP. Whereas the crude GEP had a size of approximately 700 kDa, the partially purified GEP behaved on Ultrogel AcA 54 as a protein of 60 kDa. With purification, the GEP activity became insensitive to brefeldin A, consistent with the conclusion that, in contrast to earlier inferences, the exchange protein is not itself the target of brefeldin A.